Prevalence and Risk Factors of Iron Deficiency Anaemia in Children admitted in a Tertiary Care Hospital of Bangladesh - Hoque, MM; Ahmed, ASMNU; Quaderi, H (Journal of Nepal Paediatric Society, 2015)
Introduction: Anaemia is a common problem in childhood. In Bangladesh, overall 68% of children aged 6-59 months are anaemic. Anaemia impairs normal growth and development, decreases physical exercise tolerance and intellectual performance in children. The objective of this study was to find out the prevalence and risk factors for iron deficiency anaemia in hospitalized children aged 6 to 36 months. Materials and Methods: Eligible children admitted in Dhaka Shishu (Children’s) Hospital due to any acute illness, were enrolled from 1st June 2010 to 30th August 2010. Anaemia (Hb <11gm/dl) was classified as microcytic, normocytic or macrocytic. Peripheral blood film, serum ferritin, haemoglobin electrophoresis, serum C-reactive protein and stool microscopy were done. Risk factors were looked for in cases of iron deficiency anaemia. Results: Among 331 enrolled children, 201 (61%) had anaemia, among them 63 (31%) had iron deficiency anaemia. Lower the socioeconomic status, higher was the rate of anaemia. Prematurity and low birth weight was significantly associated with anaemia. Poor feeding practices including colostrum rejection, non-exclusive breastfeeding, early/late weaning and inappropriate weaning diet were important risk factors. Gender was not found as a risk factor. Conclusion: A large proportion of hospitalized children under three years of age were found anaemic, among them iron deficiency anaemia was most common. The study result emphasizes the importance of identifying the risk factors of anaemia in this age group. Raising awareness of the problem and providing health and nutrition education will be the key interventions to prevent and control this huge public health problem in Bangladesh. J Nepal Paediatr Soc 2015;35(1):38-43